Analisis Kesiapsiagaan Masyarakat dalam Menanggulangi Bencana Alam di Indonesia (Studi pada Bencana Alam di Sumatera Utara) - Meili, Maya; Sembiring, Zamalludin (Lembaga Yasin AlSys, 2025)
This research is motivated by concerns and also the number of natural disasters in Indonesia, including the North Sumatra region which is prone to various types of disasters such as earthquakes, floods, and volcanic eruptions. Community preparedness plays an important role in efforts to mitigate disaster risk and reduce its impact. This study aims to analyze the level of community preparedness in dealing with natural disasters in several vulnerable areas in North Sumatra and the factors that affect them. The method used is a qualitative descriptive approach with data collection through interviews, observations, and documentation, with analysis using the theory of B Miles and Huberman. The results show that the level of community preparedness is in the category of